Model reference adaptive control of unknown plants using dynamic neural networks - Rovithakis, George A.; Christodoulou, Manolis A. (Zielona Góra: Uniwersytet Zielonogórski)
A direct non-linear adaptive controller solving the tracking problem for unknown dynamic systems which are modelled by dynamic neural networks is discussed. A complete model matching case is examined and convergence of the control error to zero plus boundedness of all signals in the closed loop are ensured.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka